Work from Home (WFH), COVID-19, and Its Impact on Women - Chakraborty, Debarun; Altekar, Shrirang (Prabandhan: Indian Journal of Management, 2021)
COVID-19 may have forever transformed the way we work by changing views toward working from home (WFH). Half of the individuals who were employed before the pandemic are now working remotely. A rising number of organizations, including Facebook and Twitter, announced that they would allow people to work remotely permanently as they see for themselves that quality work can be done remotely. Productivity can be increased even in occupations that no one dreamed could be done online. Under these circumstances, women have been disproportionately affected by the pandemic. Women’s domestic experiences, health, job, and financial well-being have all been badly impacted. The pandemic has not only hampered women in the present, but it has also harmed their prospects. This commentary discussed the increased implications of work from home connected with COVID-19, and that the impacts on women need to be understood urgently.